2020
DOI: 10.1051/kmae/2020013
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and genetic characterisation of Corsican and Sardinian trout with comments on Salmo taxonomy

Abstract: Both morphological and molecular data are presented and discussed for indigenous Salmo sp. from Corsica and Sardinia, here called Tyrrhenian trout. For comparison, morphological data obtained from museum specimens, including the Algerian S. macrostigma, are discussed in the light of recent and new molecular findings. In total, 29 measurements and 20 meristic characters were taken from each specimen. Out of the meristic characters, 12 were obtained by means of X-ray. One important morphometric character in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Corsica was naturally colonized by two freshwater species, the Salmo cf. trutta complex and S. fluviatilis , but the catadromic eel ( Anguilla anguilla ) is also widespread (Delling et al., 2020; Roché, 2001). The island is considered as the southernmost area that has been partly covered by an ice sheet during the LGM (Conchon, 1988; Kuhlemann et al., 2005) and was not connected to the mainland during this period (Patarnello et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Corsica was naturally colonized by two freshwater species, the Salmo cf. trutta complex and S. fluviatilis , but the catadromic eel ( Anguilla anguilla ) is also widespread (Delling et al., 2020; Roché, 2001). The island is considered as the southernmost area that has been partly covered by an ice sheet during the LGM (Conchon, 1988; Kuhlemann et al., 2005) and was not connected to the mainland during this period (Patarnello et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, many molecular phylogeneticists and phylogeographers question this biological species concept of taxonomic diversity of the genus Salmo by pointing to negligible and/or weak genetic differentiation among some of those populations/taxa (to cite from numerous ones e.g., [13,89,[94][95][96][97][98][99]). Yet, other colleagues detected significantly larger genetic differences (e.g., [100][101][102][103][104]). How can the cytotaxonomy of the genus Salmo contribute to this debate?…”
Section: Cytotaxonomy and Diversity Of Eurasian Troutsmentioning
confidence: 91%
“…Separation was more obvious between pure Mediterranean and Atlantic lineages, while hybrid individuals tended to overlap with the Mediterranean lineage, making hybrid identification difficult. Other morphometry studies have shown that either body height (or body elongation) (Monet et al, 2006;Fruciano et al, 2014;Ninua et al, 2018), head length (Simonović et al, 2007;Delling et al, 2020), or both (Pakkasmaa, 2001;Hermida et al, 2009) are distinctive features among different lineages or forms within the brown trout complex. The present study has demonstrated that body height, head length, and eye size were the main differentiating characteristics between the Danubian trout lineage and introduced Atlantic specimens.…”
Section: Discussionmentioning
confidence: 99%
“…This wide distribution is primarily related to human interests, given its commercially importance in both aquaculture and angling (Saint-Pé et al, 2019). Eurasian brown trout exhibit high phenotypic diversity linked to their complex evolutionary history (Bernatchez, 2001;Leitwein et al, 2017), and are thus often referred to as the brown trout complex (Delling et al, 2020). This diverse evolutionary history results from the ability of brown trout to use the sea and coastal zone to migrate long distances in the past, successfully invading suitable habitats (Berrebi, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation